THE VIRUS - THE TYPE OF INFECTIVE AGENT IN THE PATHOLOGY OF THE ORAL MUCOSA:A SISTEMATIC REVIEW AND DATA SYNTHESIS - Kamel Earar; Mihaela Cezarina Mehedinți; Mădălina Roxana Onea; Ana Maria Zaharescu; Anca Bejan; Shalalfeh Mohammad (Romanian Dental Association for Education, 2020)
A weakened immune system and increased exposure to germs make us vulnerable to diseases in the cold season. The cold season brings health problems for everyone, especially for the elderly. Therefore, it is important to take precautionary measures before you get sick. Via a new study, the different segments of the genome of the virus may exist in distinct cells, but may work together to cause an infection. It has been suggested that a virus genome enters a single cell and multiplies, and then moves to other cells to reproduce again. Viruses that have the ability to multiply are intriguing viral systems because their genome is divided into more many segments, and each is enclosed in a distinct particle of the virus. In the past, they believed that all segments of the genome must move together from cell to cell to cause an infection. However, the current study shows that this is not the case. Viruses are among the simplest and smallest microorganisms that infects the human body. They are made up of a nucleocapsid or virus core, the account holding the material nuclear cell (RNA or DNA), and the envelope of the virus that has specific molecules through which the microorganism attaches to the surface of certain cells - so -called ligands. In this way viruses have specificity for a certain type of cell, a property called tropism. So, all herpes viruses have tropism for epithelial cells.